'A serious place': Wyndham Lewis, Tarr, and the Café. Issue 4 (7th June 2017) - Betsworth, Leon
ABSTRACT: This article explores the significance of the café in Wyndham Lewis's first published novel, Tarr (1918). Charting the importance of the space upon Lewis's formative life as a student in Europe and later among his literary peers, it proposes that Lewis has an idealised conception of the café, which stems from the legacy of the coffeehouses of the seventeenth and eighteenth century and the Russian tavern from Dostoevsky's The Brothers Karamazov (1880). By comparing these ideals against the contemporary milieu in which Lewis found himself, we gain greater insight into the rhetorical intentions for the novel, such as the assault on bourgeois-bohemian café culture, as well as ultimately discovering that Lewis's conception of the café has a fundamental role in the construction and form of the novel itself.